Harnessing the Power of Learning Management Systems: An E-Learning Approach for Professional Development - White, Meagan; Shellenbarger, Teresa (Journal for nurses in professional development, 2017)
E-learning provides an alternative approach to traditional professional development activities. A learning management system may help nursing professional development practitioners deliver content more efficiently and effectively; however, careful consideration is needed during planning and implementation. This article provides essential information in the selection and use of a learning management system for professional development.